Are You Superstitious? A Survey on Chinese Attitudes towards Homophonic Word Taboo - Andrew, Yau-hau Tse (2011)
Taboo is the prohibition of an act or the use of a word under pain of punishment. Freud (2000) perceives taboo as superstition owned by the barbarians. This paper is a combination of socio-psychological and linguistic study since homophonic word taboo is a socio-linguistic phenomenon in Chinese culture. The objective of this piece of research is to investigate Chinese attitudes towards homophonic word taboo in Hong Kong. Questionnaires were distributed to 7 groups of students, old and young, male and female, with questions related to number 4, which is phonologically linked to the meaning of ‘death’ in Chinese culture. The Chinese people are afraid of this; therefore, they try to avoid any thing or object dealing with number 4. The findings revealed that old female students were more superstitious than young students; no significant difference was found between old male students and old female students; young male students and young female students were comparatively not superstitious. This study was conducted in Hong Kong with Hong Kong Chinese. Further study can be done in other Asian countries using Chinese as subjects. To conclude, superstition is a social phenomenon and further research is needed to investigate the realm of word taboo in sociolinguistics and psycholinguistics. Keywords: taboos, superstition, sociolinguistics, psycholinguistics